The impact of agricultural insurance on consumer food safety: empirical evidence from provincial-level data in China - Ruan, Peiheng; Yin, Sihan; Zhang, Yongchang (Frontiers in Nutrition, 2024)
In the exploration of the efficacy of agricultural subsidy policies, agricultural insurance, as a key element of this policy system, has garnered widespread attention for its potential impact on consumer food safety. This paper delves into the influence of agricultural insurance on the safety of food consumed by individuals, based on provincial panel data in China from 2011 to 2021. The findings indicate that agricultural insurance significantly reduces the incidence of foodborne disease and enhances food safety. Mediating effect tests reveal that agricultural insurance effectively boosts food safety through two key pathways: promoting innovation in agricultural technology and reducing environmental pollution. Moreover, the analysis of moderating effects highlights that increased consumer confidence positively enhances the impact of agricultural insurance. Heterogeneity tests further show that in the provinces with higher levels of agricultural development and stronger government support for agriculture, the role of agricultural insurance in improving food safety is more pronounced. This research not only empirically verifies the effectiveness of agricultural insurance in enhancing food safety but also provides robust theoretical support and practical guidance for the precise formulation and effective implementation of agricultural subsidy policies, particularly agricultural insurance policies, offering significant reference value for policy-makers.